Does organic certification make economic sense for dairy farmers in Europe?–A latent class counterfactual analysis. (27th July 2021) - Grovermann, Christian; Quiédeville, Sylvain; Muller, Adrian; Leiber, Florian; Stolze, Matthias; Moakes, Simon
Abstract: Certification in agriculture ensures compliance with tangible standards and should generate economic opportunities for farmers. This study quantifies the variable profit and efficiency impacts of organic certification in dairy farming across Europe, using farm‐level FADN data from 25 countries while accounting for heterogeneity through a class splitting model. Four distinct classes with dairy farm enterprises operating under similar production conditions were identified in order to assess gross margin and efficiency differences among certified and non‐certified farms. Depending on the nature of the selection bias, treatment effects were estimated either through an endogenous treatment model or through entropy balancing. The results suggest that organic certification increases gross margins for dairy farm enterprises in Europe, while slightly increasing technical efficiency in two out of four classes. These significant effects of certification on efficiency were estimated at 2% and 7%, respectively. As regards variable profit, effects range from to 66 Euros per cow to 234 euros per cow. In relative terms, this implies gains between 38% and 50% for farms classified into more cool or temperate zones and a gain of up to 182% for the farms assigned to the class that designates warmer climatic conditions.